Using solar energy in agriculture and livestock: cleaner production and energy efficiency - Guzmán-Hernández, Tomás de Jesús (2016)
New clean energy alternatives to mitigate the greenhouse effect and achieve real clean production are currently being sought. Among these alternatives, solar energy and use of biomass and other renewable sources have been recommended for their effectiveness in adaptability to climate change and local carbon sequestration.This paper presents the design and preliminary results of a thermal system installed in a milk factory and dairy processing plants located in the North Huetar Region of Costa Rica. The generated data show the potentiality of energy production by solar energy systems in agricultural activities. These preliminary results have shown that these systems make it possible to produce about 30% of the energy needed for these activities, thereby allowing reduce production costs, emission of greenhouse gases and, consequently,  carbon footprint.